1995
DOI: 10.2527/1995.7341002x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of non-additive genetic variances in three synthetic lines of beef cattle using an animal model2

Abstract: Dominance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…The fairly high heritabilities, arising from large genetic variances due to the multibreed composition of the herd could have been expected, since the population consists of 15 breeds, and this effect was not accounted for by the model. Rodriguez-Almeida et al (1995) reported quite variable estimates in different herd-line combinations. They suggested that the variable estimates might be due to the inclusion of non-additive genetic variances.…”
Section: Resultsmentioning
confidence: 99%
“…The fairly high heritabilities, arising from large genetic variances due to the multibreed composition of the herd could have been expected, since the population consists of 15 breeds, and this effect was not accounted for by the model. Rodriguez-Almeida et al (1995) reported quite variable estimates in different herd-line combinations. They suggested that the variable estimates might be due to the inclusion of non-additive genetic variances.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of nonadditive genetic variance in evolution by natural and artificial selection is controversial Crow 2010;Hansen 2013). Nevertheless, numerous studies have found and exploited dominance and epistasis in animal breeding, including dairy (Ahlborn-Breier and Hohenboken 1991;Fuerst and Sölkner 1994;Varona et al 1998;Van Tassell et al 2000;Palucci et al 2007) and beef (Rodriguezalmeida et al 1995) cattle. Diallelic studies have indicated significant SCA for maize grain yield (Doerksen et al 2003;Wardyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Parameter estimation in domestic breeds has frequently included the maternal additive genetic variance, direct maternal additive genetic covariance and maternal environmental variance (e.g., see Clément et al, 2001) and this model was fitted to the feral population of Soay sheep (Wilson et al, 2005). Additionally, non-additive variances have been estimated for domestic breeds (e.g., Rodriguez-Almeida et al, 1995). The theory for the construction of the relevant matrices for the inclusion of sex-linked effects has been worked out by Grossman and Fernando (1989) and Fernando and Grossman (1990).…”
Section: Dj Fairbairn and Da Roffmentioning
confidence: 99%